Factors contributing to stress in clinical practices: A proposed structural equation model - Manuel Sánchez de Miguel; Aintzane Orkaizagirre‐Gómara; Javier Ortiz de Elguea; Andrea Izagirre Otaegi; Amaia Ortiz de Elguea‐Oviedo (Wiley, 2020)
Abstract Aim To propose a predictive model of procedural and emotional stress in clinical placements while testing self‐efficacy as a possible mediator factor. Design The study used an exploratory correlational design. Method A total of 334 nursing students completed the KEZKAK-stress in clinical practice, AG-general self‐efficacy and CEA-academic overload questionnaires, along with one about leadership. Sociodemographic information was also included. Results Confirmatory factor analyses and internal consistency reliabilities were satisfactory in all questionnaires. Procedural stress and emotional stress were confirmed by KEZKAK [χ2 (674) = 1,555.58, p = .001; χ2/df = 2.308, CFI = .90, IFI = 91, RMSEA = .06]. The structural equation method for procedural stress and emotional stress had an acceptable fit. They revealed that academic level influenced the perception of leadership and academic overload in both procedural stress and emotional stress. General self‐efficacy only mediated emotional stress. Hospital unit acted independently as a predictor of procedural stress.